Impacts of fixed orthodontic appliance and clear-aligner on daily performance in adult patients with moderate need for treatment - Lin F (Patient Preference and Adherence, 2016)
Feiou Lin,1 Linjie Yao,2 Chandradev Bhikoo,1 Jing Guo3 1Department of Orthodontics, 2Department of Pedodontics, School of Stomatology, Wenzhou Medical University, Wenzhou, 3Department of Orthodontics, School and Hospital of Stomatology, Shandong University, Jinan, People’s Republic of China Objective: To assess the impact of wearing fixed orthodontic appliance (FOA) or clear-aligner, on daily performance in adult patients. Methods: The Oral Impacts on Daily Performance (OIDP) index was assessed in 152 adults aged 25–35 years at baseline (T0), 6 months after bonding (T1), and 12 months after bonding (T2). Participants were randomly divided into two groups: CA group (participants treated with clear-aligner) and a control group (FOA group; participants treated with FOA). Baseline malocclusion severity was assessed using the Index of Orthodontic Treatment Need. Results: There were no significant differences in sociodemographic variables and OIDP scores at baseline between the two groups. Significant changes in OIDP total and subscale scores were observed while wearing FOA: OIDP total score and subscale scores of eating, cleaning teeth, smiling, and social relation at T1 and T2 were significantly higher than at baseline (P<0.05 or P<0.01). However, only OIDP total score was significantly increased at T1 compared to the baseline in the CA group. OIDP total score and subscale scores of eating, cleaning teeth, smiling, and social relation were significantly higher in patients wearing FOA than in patients wearing clear-aligner at T1 and T2 (P<0.05 or P<0.01). Conclusion: Patients wearing clear-aligner have fewer impacts on daily life than those wearing FOA during treatment, and have no significant changes in OIPD subscale scores at 12 months. FOA therapy significantly impacts daily performance in adult patients during treatment. Keywords: clear-aligner, fixed orthodontic appliance, OIDP, quality of life, oral health